A Revision of the New World genus Lepidophora Westwood, 1835 (Diptera, Bombyliidae, Ecliminae) with a key to the species - Rodrigues, Paula Fernanda Motta; Lamas, Carlos José Einicker (Zootaxa, 2013)
The bombyliid genus Lepidophora has a distribution restricted to the New World. The genus is composed by eight species, which are revised and redescribed herein: five restricted to the Neotropical region (L. acroleuca Painter, 1930, L. culiciformis Walker, 1850, L. cuneata Painter, 1939, L. secutor Walker, 1857 and L. trypoxylona Hall, 1981), two restricted to the Nearctic region (L. lepidocera (Wiedemann, 1828) and L. lutea Painter, 1962) and one species occurring in Nearctic and Neotropical regions (L. vetusta Walker, 1857). The main characters of the external morphology of adults and male and female terminalia are illustrated. An key to species is presented.